(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
One of the keys to students’ success in studying is to prioritize a patient attitude in facing all existing obstacles. This discussion aims to explore the values ​​of patience in the Qur’an, especially in seeking knowledge. This research was carried out by examining the verses of the Qur’an relating to patience, then studying the meaning and interpretation of these verses and looking for references related to the topic of discussion and articles relevant to the concept of patience in seeking knowledge, both in books written by scholars and works written by Muslim scholars. This discussion uses literature study, where research result taken from the text of the verses of the Qur’an is then linked to the research objectives to be obtained, namely the concept of patience in the Qur’an in seeking knowledge. The existing research result is analyzed in such a way using descriptive analysis techniques. and then interpreted in the conclusion discussion. The research results show that patience is a very important thing for students to have in the demands of knowledge. A student must develop a patient attitude in learning, because patience is the key to success, patience also gets huge rewards as promised by Allah SWT. Furthermore, students must be able to stay for a long time to complete one science study. There are several ways that students can develop a patient attitude in studying, including increasing self-awareness, sharpening emotional intelligence, preventing desires and momentary pleasures, maintaining responses, harmonizing thoughts and actions and increasing spirituality within oneself.